DETERMINATION OF THE BOND’S WORK INDEX OF BABAN TSAUNI (NIGERIA) LEAD-GOLD ORE - Egbe, E.A.P.; Mudiare, E.; Abubakre, O. K.; Ogunbajo, M.I. (European Scientific Journal, ESJ, 2013)
The energy required to grind one tonne of an ore from a given feed size to a specified product size is a material property that needs to be determined for different ore deposits. The Bond’s work index has generally been accepted as a measure of the grindability of an ore. This study used quartz as a reference ore via a comparative method to determine the Bond’s work index of Baban Tsauni Nigeria) ore. The same amount of energy was utilized in grinding the reference and test ore with the same particle size distribution under the same grinding conditions. Typical feed load and mill speed in practice were used in order to make the grinding environment as close as possible to that in large scale grinding. The Bond’s work index of Baban Tsauni (Nigeria) ore was found to be 11.52kWh/tonne.